PEMASARAN DIGITAL BERBASIS INFLUENCER, PENGARUHNYA TERHADAP MOTIVASI KUNJUNGAN WISATAWAN DOMESTIK KE DESTINASI WISATA DI NUSA PENIDA - Ni Nyoman Menuh; Ni Made Nia Kristyarini (STIMI Handayani Denpasar, 2020)
Influencer is one of the factor in the success of digital marketing through social media in Indonesia. It happens because of the high number of people who use social media and their tendency to be influenced by influencers. There is many managers who use this strategy to attract domestic tourists and Nusa Penida is one of the tourist destinations that are often uploaded by influencers. This study aims to determine and analyze the effect of influencer-based digital marketing on the domestic touristmotivation to travel to the tourist destinations in Nusa Penida. The type of data is quantitative with primary data sources. Data is collected by filling out the questionnaires, then being analyzed using quantitative descriptive analysis, includes validity test, reliability test, classic assumption test, simple linear regression test, correlation test, coefficient of determination test and hypothesis test (t-test). The results indicatethere is a significant impact on the tourist motivation to travel to the tourist destinations in Nusa Penida after the existence of influencer-based digital marketing.